Identity, relationship quality, and subjective burden in caregivers of persons with dementia. (25th October 2018) - Enright, Joe; O'Connell, Megan E; Branger, Camille; Kirk, Andrew; Morgan, Debra
The aim of the current study was to examine the associations between informal caregivers' perception of identity change in their care-partner, the quality of the caregiver/care-recipient relationship, and caregiver burden in a sample of 56 informal caregivers of persons with dementia. Most (96.4%) of the caregivers of persons who received a dementia diagnosis reported a perceived change in the identity of their care-partner. Caregivers' perception of relationship satisfaction was measured with the Burns Relationship Satisfaction Scale for premorbid relationship and current relationship quality, and caregiver burden was measured with the Zarit Burden scale. After controlling for variance due to dementia severity, premorbid relationship satisfaction, and current relationship satisfaction, caregivers' perceived change in the identity of the person with dementia accounted for significant variance in caregiver burden. Using a mediational model, we found support for a direct effect between perceived change in identity and caregiver burden, but we also found support for an indirect effect of relationship quality on the relation between perceived identity change and caregiver burden. The demonstrated model provides an empirically supported theoretical framework for guiding potential research and development of future interventions, which we suggest should emphasize dyads.